The Business Analysis of Electric Vehicle Charging Stations to Power Environmentally Friendly Tourism: A Case Study of the Khao Kho Route in Thailand - Insan, Dokrak; Rakwichian, Wattanapong; Rachapradit, Parichart; Thanarak, Prapita (International Journal of Energy Economics and Policy, 2022)
The growing demand for electric vehicle charging stations is due to the increasing number of electric vehicles due to the rapid development of electric vehicle production and people buying more. This has also increased the demand for electric vehicle charging stations to travel between cities. This is because most combustion cars nowadays use fossil fuels. It harms clean air, producing carbon dioxide (CO2), PM2.5, and greenhouse gas emissions, resulting in climate changes and natural environmental impacts. Directly affect people in terms of health, living, and present life. By emphasizing the participation of business and government sectors, Thailand has encouraged investment in producing and importing electric vehicles to replace fossil fuel combustion. They also promoted the development of electric cars to be more efficient and run longer distances. The cumulative number of electric vehicles from 2017 to the present is increasing, making business opportunities for EV charging stations available in Thailand. From business model analysis was designed in 3 scenarios, resulting in Scenario1 Normal charger 6 outlets, in which the cost is low, the cost recovery time is the most, and it has a low net profit margin installed in shopping malls, restaurants, and residential condominiums. Scenario2 Quick charger 6 outlets take less time to charge. A high charging and increased investment cost have a short payback period installed in front of convenience stores and the current gas station. Scenario3 is a combination of an electric vehicle charging station with a normal charger and quick charger total of 2 outlets, installed in large areas such as current gas stations, logistics centers, and department stores with souvenir shops and convenience stores. This information can help analyze costs and plan investment decisions on the ownership of electric vehicle charging stations. In addition, electric vehicle charging station scenarios can be compared to predict the net profit margin of the business model.